Mastery of the determinants by 5th AP and 4th AM learners. - Louiza , Louiza (Journal of Human Sciences, 2020)
This research falls within the framework of the didactics of the FLE, and more specifically in the teaching of grammar. In this modest work we were interested in evaluating the skills of primary and secondary school leavers at the level of the determinants and this through written productions, in order to see how these learners reuse the knowledge acquired in class and the difficulties encountered in their learning of the concept in question.